Using remote tracking technologies to audit and understand medicine theft - Ryan Jablonski; Brigitte Seim; Mariana Carvalho Barbosa; Clark C. Gibson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Medicine theft is a leading cause of inadequate healthcare. Audits of public health supply chains suggest that up to a third of medicines go missing in low-income countries, disproportionately affecting those facing greater health risks and poverty. Despite much investment, policy-makers struggle to identify and prevent theft due to the opaque and highly distributed supply chain in most low-capacity health systems. We propose a technology-based audit tool-a 'remote tracking audit'-to address these challenges and to provide new insight into the causes and consequences of theft. We evaluate this tool in Malawi, a context where over two thirds of communities have observed the illegal sale of medicines. We partner with the Ministry of Health to place electronic tracking devices in 2,387 medicine boxes. The devices provide real-time data on medicine locations and provide some of the most comprehensive estimates to date on the scale, timing, and consequences of medicine theft. We estimate that 35% of medicines go missing. Most theft occurs after deliveries, presumably by public health staff. However, supply chain error is the most common cause of missing medicines. We show that patients experience higher stock-outs and pay more for medicines near facilities with more theft. These findings confirm that theft is a severe public health problem but suggest policy-makers could also productively redirect anti-theft investments towards closing supply chain gaps. The study also illustrates how remote tracking technologies can be an effective tool in the anti-theft arsenal.
Keywords: O10; O38; O55; P00; 330; corruption; health systems; drug theft; monitoring; Malawi